Investigation on the multiple plies structure of aluminum-lithium alloy and glass fiber composite with respect to deformation failure - Qutaba, Syed; Asmelash, Mebrahitom; Azmir, Azhari (IOP Publishing Ltd, 2023)
The deformation behavior and mechanical properties based on the aluminum-lithium alloys (FMLs) was investigated to optimize the manufacturing process and further interface interaction. The primary structures of the FML composites were made with two sets of plies. From there, six secondary composites with different fibre sheet orientations were made. Then, interlaminar tensile, flexural, and peeling properties of FMLs were tested. The fiber orientation role in the case of failure behaviors of FMLs under different conditions was also revealed. The results have indicated that the plies design significantly enhanced the interlaminar properties of the FMLs and orientation of fiber laying has significantly affected the flexural strength. The peeling test has shown higher fiber-to-metal interfacial bonding with the value of ≥80 N m−2 over metal-to-metal adhesion. The plies increase the mechanical properties of composite based at fiber orientation and thickness, but too much impairs performance. The 3/2 plies showed a value of ≤385 MPa, which has better results in axial structure analysis than over 4/2 composite layers. The peak values appeared under different parameters like adhesive bonding and parallel fiber orientation, represented in the qualitative analysis section. The surface microscopy of aluminum-lithium alloy sheet and cross-section failure morphology of composite has been done at a different sighting. Surface characterization, fiber orientation breakdown, and deformation morphology have been studied concerning alloys' elongated grains and micro pits.